Assessment of plant response capability in the event of loss of electrical power and loss of ultimate heat sink. (15th September 2022) - Kim, Chang Hyun; Kim, Seyun; Choo, Bong Sik; Song, Jun Kyu
Highlights: This paper presents the stress test method developed for Korean nuclear power plants focusing assessment method of plant response capability to the loss of safety functions due to extended loss of AC power (ELAP) and loss of ultimate heat sink (LUHS). This paper also shows assessment results of plant response capability in the events of ELAP and LUHS of OPR1000 that is a standardized PWR by Korea based on the ABB-CE System 80. Multi-barrier accident coping strategy (MACST) guidelines have been developed to accomplish specific tasks in support of emergency operating procedures (EOP) when the extended loss power AC power and/or loss of ultimate heat sink is in progress as a consequence of beyond design basis natural events. Safety provisions to secure critical safety functions are presented with cliff edge time evaluation at each step of plant response to extended loss of AC power and loss of ultimate heat sink. Abstract: This paper presents a stress test method developed for Korean nuclear power plant and assessment results of plant response capability of OPR1000 in an effort to enhance the safety against extreme natural events exceeding the design basis of the plant. Multi-barrier accident coping strategy (MACST) guidelines have been developed to accomplish specific tasks in support of Emergency Operating Procedures (EOP) when the Extended Loss of AC Power (ELAP) and/or Loss of Ultimate Heat Sink (LUHS) is in progress as a consequence of beyond design basis natural events. Provisions to secure critical safety functions are discussed with cliff edge time evaluation at each step of plant response to ELAP and LUHS. It is concluded that the plant can maintain the safe shutdown state through the natural circulation cooldown by steam generator and the electric power and can obtain additional capability and redundancy with off-site equipment to provide coping capability for an indefinite period.